The Key Issues of the Execution of the Arbitral Awards in the Republic of Armenia - Hovhannisyan, Vahe (Bulletin of Yerevan University C: Jurisprudence, 2023)
In this scientific article, the author investigated and observed the arbitral awards enforcement regimes on the territory of the Republic of Armenia. Observation of the legislation of the Republic of Armenia in the relevant field revealed features of state compulsory enforcement of arbitral awards of ad hoc institutions on the territory of the Republic of Armenia, permanent arbitration awards and finally arbitration tribunal decisions not exceeding the minimum wage by five thousand time. Some valuable recommendations have been made to improve voluntary enforcement of arbitral awards.The contemporary issues of co-called domestic arbitral awards state compulsory enforcement have been discussed in comparison with western developed countries legal practice. In the article, the author made some suggestions regarding improvement of the legislation on commercial arbitration, mainly concerning the protection of subjective rights.Moreover, the author presented the practical guideline how to exclude by law the private entity eligibility of state compulsory enforcement.
Keywords: Arbitral award; voluntary enforcement; compulsory enforcement; writs of execution; deferred judicial review; commercial arbitration; ad hoc arbitration